2017
DOI: 10.31018/jans.v9i4.1489
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of biogas production from water hyacinth (Eichhornia crassipes)

Abstract: Abstract:The present investigation reports the optimization of process parameters for biogas production from water hyacinth (Eichhornia crassipes). The different parameters like particle size, inoculum concentration, incubation temperature, metal ions and pH were optimized for biogas production. Maximum biogas was observed with water hyacinth of 1cm size, 40 % inoculum concentration. The temperature of 45°C along with neutral pH i.e. 7 was found to be most suitable for biogas production in the presence of mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…Methane is produced by anaerobic methanogens, which are very sensitive to changes in environmental conditions such as pH and temperature. Optimal activity of methanogens in previous studies has been recorded at pH 6.5–7.5 and this supports the results of this study where the pH of most of the treatments (digestate) was in an optimal range that supported the growth of methanogens suggesting stability of the AD process (Rozy et al 2017 ; Cerón-Vivas et al 2019 ). Increased pH relates to accumulated ammonium, however, the presence of accumulated ammonia in the digesters though toxic to methanogens, further supports the utilization of the resultant digestate as a soil ameliorant (Zhang et al 2017 ; Adeleke et al 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Methane is produced by anaerobic methanogens, which are very sensitive to changes in environmental conditions such as pH and temperature. Optimal activity of methanogens in previous studies has been recorded at pH 6.5–7.5 and this supports the results of this study where the pH of most of the treatments (digestate) was in an optimal range that supported the growth of methanogens suggesting stability of the AD process (Rozy et al 2017 ; Cerón-Vivas et al 2019 ). Increased pH relates to accumulated ammonium, however, the presence of accumulated ammonia in the digesters though toxic to methanogens, further supports the utilization of the resultant digestate as a soil ameliorant (Zhang et al 2017 ; Adeleke et al 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Patil et al (2011) performed the anaerobic digestion of natural water hyacinth with different amounts of water, observing a maximum biogas yield of 0.245 l/g VS when using water hyacinth slurry in a ratio of 1:4, in the mesophilic temperature range of 30 °C-37 °C for 60 days. Rozy et al (2017) reported a biogas production of 0.045 l/g water hyacinth, 0.3601 l/g TS, and 0.398 l/g VS in optimal conditions within 40 days. O' Sullivan et al (2010) obtained a biogas production potential of 0.2-0.4 l/g VS with water hyacinth.…”
Section: Daily Biogas Productionmentioning
confidence: 98%
“…Lag phases were attributed to methane precursors’ consumption by methanogens for growth or the accumulation of volatile fatty acids that led to short‐term inhibition of the digestion process, while the peaks were attributed to the varying levels of digestibility of the substrates. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] The dried WH (leaves, stems, and roots) was then cut into smaller pieces of about 1–5 cm to increase the surface area of the WH for easy biodegradability. According to Rozy et al., [ 21 ] optimization of different WH particle sizes (1–3 cm) may help to increase active sites for methanogens to grow resulting in higher biogas yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation